PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL PEMEDIASI (Studi Eksplorasi pada Karyawan Usia Muda di Kota Pontianak) - Jonathan Giovanni (Jurnal Ekonomi Integra, 2018)
This study examines the possibility of becoming a mediator variables on the influence of transformational leadership on employee performance. Respondents were 110 young employees around Pontianak City. Data will be analyzed with path analysis method that would prove the effect of each variable to another variable. The analysis showed that work engagement are variables that mediate the effects of transformational leadership on employee performance. These results provide input for the management of any organizastion to give more confidence and space for employees to work which will lead to increased work engagement impact on the performance of employees.